Learn American sign language : everything you need to start signing now - Guido, James W. (Wellfleet Press, 2015)
American Sign Language (ASL) is a vibrant, easy-to-learn language that is used by approximately half a million people each day. Current with the latest additions to ASL and filled with thousands of brand new photographs by Deaf actors, Learn American Sign Language is the most comprehensive guide of its kind.- Learn more than 800 signs, including signs for school, the workplace, around the house, out and about, food and drink, nature, emotions, small talk, and more.- Unlock the storytelling possibilities of ASL with classifiers, easy ways to modify signs that can turn "fishing" into "catching a big fish" and "walking" into "walking with a group."- Find out how to make sentences with signs, use the proper facial expressions with your signs, and other vital tips.